2021
DOI: 10.12968/ajmw.2020.0023
|View full text |Cite
|
Sign up to set email alerts
|

Timing and factors associated with early antenatal visits among pregnant women in west Gojjam, northwest Ethiopia

Abstract: Background Early and appropriate antenatal care practices have the potential to save the lives of mothers and their children, and enable mothers to receive the full range of antenatal care services. However, in developing countries, including Ethiopia, a number of pregnant women do not attend antenatal care in the recommended time period. Therefore, this article assessed the timing and factors associated with early antenatal care visits in west Gojjam, northwest Ethiopia. Methods An institution-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…This study finding showed that approximately 63% of women had scheduled their ANC visits timely (4 months and earlier). This study finding was higher than those of studies carried out in Bahir Dar city (44.2%), Sodo(39%), west Gojam (31.5%), Ethiopia (26.8%), Nigeria (24%), southeastern Tanzania (29%), Malawi (28%), Gondar (47.4%), and Tigray region (27.5%) ( 1 , 3 5 , 7 , 13 , 20 22 ). Similarly, these findings were higher than the results of the study conducted based on the 2016 EDHS that approximately 20% of the mothers initiated ANC timely, Bangladesh (43%) and South Sudan (14.1%) ( 6 , 23 , 24 ).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This study finding showed that approximately 63% of women had scheduled their ANC visits timely (4 months and earlier). This study finding was higher than those of studies carried out in Bahir Dar city (44.2%), Sodo(39%), west Gojam (31.5%), Ethiopia (26.8%), Nigeria (24%), southeastern Tanzania (29%), Malawi (28%), Gondar (47.4%), and Tigray region (27.5%) ( 1 , 3 5 , 7 , 13 , 20 22 ). Similarly, these findings were higher than the results of the study conducted based on the 2016 EDHS that approximately 20% of the mothers initiated ANC timely, Bangladesh (43%) and South Sudan (14.1%) ( 6 , 23 , 24 ).…”
Section: Discussioncontrasting
confidence: 67%
“…Globally, pregnancy-related complications accounts for 300,000 maternal deaths ( 1 ). Maternal mortality is a major health problem in sub-Saharan Africa, and Ethiopia is one of the countries with the highest maternal mortality ratio of 412/100,000 ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, it is best to begin iron and folic acid supplementation as soon as possible. Most Ethiopian women do not begin iron folic acid supplementation during the first trimester of pregnancy because the majority of them discover their pregnancy after the first trimester and begin ANC during the second half of pregnancy (36).…”
Section: Discussionmentioning
confidence: 99%
“…FP/RH is a key, and often unfulfilled need of women and girls in humanitarian settings [30,31]. Prior to COVID-19 there was a large unmet need for FP/RH services among internally displaced women and girls in Nigeria [32][33][34]. This is especially true for adolescent girls and young women who are more vulnerable to poor sexual and reproductive health outcomes and have few services tailored to their specific needs [33,35,36].…”
Section: Discussionmentioning
confidence: 99%